Simultaneous optical and radar observations of meteor head-echoes utilizing SAAMER - Michell, R. G. (2015)
We present simultaneous optical and radar observations of meteors observed with the Southern Argentine Agile MEteor Radar (SAAMER). Although such observations were performed in the past using High Power and Large Aperture radars, the focus here is on meteors that produced head echoes that can be detected by a significantly less sensitive but more accessible radar system. An observational campaign was conducted in August of 2011, where an optical imager was operated near the radar site in Rio Grande, Tierra del Fuego, Argentina. Six head echo events out of 150 total detections were identified where simultaneous optical meteors could also be clearly seen within the main radar beam. The location of the meteors derived from the radar interferometry agreed very well with the optical location, verifying the accuracy of the radar interferometry technique. The meteor speeds and origin directions calculated from the radar data were accurate—compared with the optics—for the 2 meteors that had radar signal-to-noise ratios above 2.5. The optical meteors that produced the head echoes had horizontal velocities in the range of 29–91 km/s. These comparisons with optical observations improve the accuracy of the radar detection and analysis techniques, such that, when applied over longer periods of time, will improve the statistics of southern hemisphere meteor observations. Mass estimates were derived using both the optical and radar data and the resulting masses agreed well with each other. All were within an order of magnitude and in most cases, the agreement was within a factor of two.